THE GRAVITY OF C.R.E.A.M STRATEGY - Ziyoda Saparbayeva Rustamboy qizi; Khudoynazarova Dildora Shonazar qizi (Web of Journals Publishing, 2024)
In this article we will get right into one of the strategies of learning called C.R.E.A.M. This actually, is an abbreviation which stands for Creative, Reflective, Effective, Active and Motivated. The data about learning strategies and the ways of productive learning are provided in this article. It is analyzed that one of the most methodical strategies that students should know is C.R.E.A.M strategy.
Keywords: C.R.E.A.M, reflexive, effective, active, critical thinking, learning strategy, independent learners.